Contemporary imaging following atrial redirection surgery for transposition of the great arteries. Issue 19 (10th June 2016) - Morrison, Margaret Louise; Lockhart, Christopher J; Grant, Brian
Abstract : Clinical introduction: A young man attended the adult congenital heart disease clinic for routine follow-up. He had a diagnosis of transposition of the great arteries (TGA) and underwent a Senning procedure at 10 months of age. He had remained well over the intervening years, was fully saturated, with a normal exercise tolerance, no cardiovascular symptoms and no history of arrhythmia or symptoms suggesting thromboembolic events. Transthoracic echocardiogram is shown in figure 1 A and cardiac MRI image in figure 1 B. Question: Which of the following is the most likely diagnosis? Intact atrial pathways Secundum atrial septal defect Baffle leak Primum atrial septal defect Baffle obstruction